Influence Of Recruitment System And Job Design On Competence And Employee Performance - Muhammad Yusuf (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
Recruitment is a vital process in the HR activity, especially within the context of State Owned Enterprises (SOEs) where profitability is not the main requirement in the business context. This study specifically aims to examine and explain the effect of the recruitment and job design systems on employee competence and performance in one the largest SOEs in West Indonesia, one of the well known cement factory- PT. Semen Baturaja Indonesia. This research is an explanatory research that explains the causal relationship between variables through hypothesis testing. The number of samples in this study, 200 employees in the production section of PT. Semen Baturaja. The data analysis used is Partial Least Square analysis with WarpPLS. The research findings show that the five proposed hypotheses are accepted which means there is a significant influence between the Recruitment System on Competence and Employee Performance, between Job Design on Competence and Employee Performance and between Competence and Employee Performance.